Direct Versus Indirect Measurement of Digit Ratio (2D:4D): A Critical Review of the Literature and New Data. (17th February 2016) - Ribeiro, Evaldo; Neave, Nick; Morais, Rosana N.; Manning, John T.
Digit ratio (2D:4D: the relative lengths of the second and fourth digits) is widely used as a correlate of prenatal sex steroids. There are two common methods of measuring 2D:4D, the direct method and the indirect method. The modern interest in 2D:4D began 16 years ago when finger lengths were measured directly, but many studies now report 2D:4D calculated from indirectly measured fingers from photocopies or scans. However, there are concerns about the accuracy of the latter in comparison to the former. The purpose of this article was twofold: to review these concerns and to add new data to the debate. Our review shows that in 2005, directional effects in indirect 2D:4D were reported such that direct 2D:4D > indirect 2D:4D. This finding was challenged by a 2006 report that direct 2D:4D was lower (not higher) than indirect 2D:4D for male right-hand 2D:4D. Two further studies from the same group have claimed that indirect 2D:4D may be lower, higher, or comparable to direct 2D:4D. More recent comparisons of direct 2D:4D versus indirect 2D:4D and a meta-analysis of Chinese studies have replicated the finding of direct 2D:4D > indirect 2D:4D. We considered an additional sample and found significant direct 2D:4D > indirect 2D:4D for three of four ratios. The overall literature is discussed within the context of standards of research (sample size) and publishing (clarity of report). It is concluded that direct 2D:4D does tend to be greater than indirect 2D:4D. Implications for comparative studies and other aspects of research in 2D:4D are discussed.